Multi-parameter control of photodetection in van der Waals magnet CrSBr - Shiqi Yang; Zhigang Song; Yuchen Gao; Leyan Huang; Xinyue Huang; Pingfan Gu; Wenjing Liu; Zuxin Chen; Yu Ye (Light: Science & Applications)
Abstract Photodetectors equipped with multi-parameter control hold the potential to deliver exceptional performance in a wide range of scenarios, paving the way for developing novel spin-opto-electronic devices. Nevertheless, the integration of such capabilities within a single device is challenging due to the necessity of harmonizing multiple materials with varying degrees of freedom. In this study, we introduce the van der Waals magnet CrSBr, featuring inherent anisotropy and distinctive spin-electronic coupling, to this realm. The linear dichroic ratio of the photocurrent in CrSBr tunneling device can reach ~60 at 1.65 K, and the photoresponse experiences a significant boost with increasing magnetic field. Additionally, the unique spin-charge coupling engenders a photon energy-dependent photocurrent that is modulated by an external field and is validated by first-principle calculations. Our findings elucidate the effective multi-parameter control of photodetection based on vdWs magnet CrSBr, highlighting its potential applications in cutting-edge optoelectronic devices and as a highly sensitive probe medium.